2012
DOI: 10.4103/0301-4738.100560
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in the prevalence of blindness and visual impairment in a rural district of India: Systematic observations over a decade

Abstract: Context:Globally, limited data are available on changing trends of blindness from a single region.Aims:To report the changing trends in the prevalence of blindness, visual impairment (VI), and visual outcomes of cataract surgery in a rural district of Andhra Pradesh, India, over period of one decade.Settings and Design:Rural setting; cross-sectional study.Materials and Methods:Using a validated Rapid Assessment of Cataract Surgical Services (RACSS) method, population-based, cross-sectional survey was done in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…18 24 25 When compared with results from a previous population-based study conducted in the same state, the prevalence of VI and blindness were about 2.5 times higher than those found in the present study 26. Only limited inferences can be made from comparison of these studies as the age groups and the study settings are different.…”
Section: Discussioncontrasting
confidence: 71%
“…18 24 25 When compared with results from a previous population-based study conducted in the same state, the prevalence of VI and blindness were about 2.5 times higher than those found in the present study 26. Only limited inferences can be made from comparison of these studies as the age groups and the study settings are different.…”
Section: Discussioncontrasting
confidence: 71%
“…In fact, population-based studies that were conducted over a decade ago in several parts of India revealed poor outcomes after cataract surgery 18 19. However, technological advances and increase in availability of cataract surgical services support by NPCB are resulting in better outcomes as evidenced by recent publications 20 21. However, efforts are needed to pass this information on to the communities using effective information, education and communication tools so that these barriers are addressed.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Only a repeat of this survey after 5–7 years could show the impact of the service delivery model in this region, through there is an evidence for this from other locations in the state. [23], [27] The Warangal district where no intervention is planned may act as a control for future comparisons.…”
Section: Discussionmentioning
confidence: 99%